2001
DOI: 10.1007/s101230100006
|View full text |Cite
|
Sign up to set email alerts
|

Screening of antimicrobial activities in red, green and brown macroalgae from Gran Canaria (Canary Islands, Spain)

Abstract: Extracts from 44 species of seaweed from Gran Canaria (Canary Islands, Spain) were screened for the production of antibacterial and antifungal compounds against a panel of Gram-negative and Grampositive bacteria, mycobacteria, yeasts and fungi. A total of 28 species displayed antibacterial activity, of which six also showed antifungal activity. Asparagopsis taxiformis and Cymopolia barbata were the species with the strongest activities against the broadest spectrum of target microorganisms. All the species wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(50 citation statements)
references
References 18 publications
6
44
0
Order By: Relevance
“…In contrast, inhibition against the fungis C. albicans and S. cerevisiae was rarely detected. These results are in agreement with those of other studies, in which microalgae and cyanobacteria were screened to detect antibacterial effect as well as macroalgae for antimicrobial activities [30,38]. …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, inhibition against the fungis C. albicans and S. cerevisiae was rarely detected. These results are in agreement with those of other studies, in which microalgae and cyanobacteria were screened to detect antibacterial effect as well as macroalgae for antimicrobial activities [30,38]. …”
Section: Resultssupporting
confidence: 93%
“…The production of secondary metabolites with antimicrobial affects was also studied using macroalgae grown under different conditions [30]. Result of these investigations showed that algae are able to produce a large number of compounds with bioactive activities.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that seaweeds possess compounds exhibiting antimicrobial potential against the pathogenic microbes of medical, agricultural, and environmental importance. Thus, antiviral, anthelmintic, antifungal, and antibacterial activities have been detected in green, brown, and red algae [58]. There are numerous reports on the biological activities of macroalgae against human pathogens, fungi, and yeast [6].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, seaweeds are considered as a source of bioactive metabolites characterized by a wide spectrum of effects (Fouladvand et al, 2011). Compounds with immunostimulant, cytostatic, antiviral, anti-helminthic, antifungal, antibacterial activities have been detected in all phyla of macroalgae (Ballesteros et al, 1992; Val et al, 2001; Smit, 2004; Talarico et al, 2004; Cumashi et al, 2007; Shanmughapriya et al, 2008; Dhargalkar and Verlecar, 2009; Kamenarska et al, 2009; Vallinayagam et al, 2009; Allmendinger et al, 2010; Bouhlal et al, 2010; Chanda et al, 2010; Vonthron-Sénécheau et al, 2011; Barman et al, 2013; de Jesus Raposo et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Although several studies focused on the antimicrobial properties of macroalgae, few studies reported on bacterial pathogens relevant in aquaculture (Val et al, 2001; Liao et al, 2003; Bansemir et al, 2006). …”
Section: Introductionmentioning
confidence: 99%